Institutionalizing Science Integration at UIN Sunan Kalijaga: Insights from Students’ Perspectives - Andrianor, Andrianor; Sari, Ramadhanita Mustika; Adhitya, Amri (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
The discourse of science integration within Islamic Higher Education Institutions (PTKI) has now entered the institutionalization phase, though it still faces conceptual and practical challenges. This study explores the institutionalization process of the science integration discourse through a case study of the Integration-Interconnection (I-Kon) idea at the Graduate School of UIN Sunan Kalijaga Yogyakarta (UIN Jogja). Using a qualitative approach and case study methodology, the research involved literature studies, interviews, and observations to understand the implementation, outcomes and factors supporting or hindering the I-Kon idea, especially from the students’ perspectives. The findings of this study reveal that the formal, informal, and hidden curricula at UIN Jogja complement each other in institutionalizing the I-Kon idea. Analysis on 334 student theses identified three main typologies: 'Linear-Concentration', 'Multidisciplinary Linear-Concentration', and 'Multidisciplinary Cross-Concentration'. The study concludes that the success of I-Kon implementation depends on students’ adaptability and the support of the academic environment. These findings offer critical insights for evaluating and developing the implementation of science integration in other PTKI.